PENGARUH KUALITAS FRIENDSHIP TERHADAP SUBJECTIVE WELL-BEING PADA USIA DEWASA AWAL - Farida, Ema Masrurotul; Tjiptorini, Sitawaty (Jurnal Ilmiah Penelitian Psikologi, 2021)
The purpose of this study was to determine the effect of friendship quality on subjective well-being in early adulthood. This is motivated by a change in personality in early adulthood which is seen from a psychosocial perspective so that friendship relations become the independent variable because there has been research that the friendship quality variable can be used as the independent or dependent variable and subjective well-being the dependent variable. The sample of this research is individuals who are in the early adulthood stage with the age of 20-40 years, whose respondents are 184 people consisting of 134 women and 50 men. The instrument used in this study is the Friendship Qualities Scale compiled by Bukowski, Hoza, & Boivin (1994) and Well-Being Scales compiled by Kobau, Sniezek, Zack, Lucas, & Burns (2010) . The data of this study were analyzed using regression analysis. The results of this study indicate that the hypothesis is proven. From the data management, it is found that the quality of friendship shows a positive influence on subjective well-being with a coefficient of R = 0.399 and a value of R Square = 0.159 or 15.9% and a sig F Change of 0.000 which means p < 0.05. This shows that the variable of friendship quality has a positive influence on subjective well-being in early adulthood.